Quantifying Ship Shape in Archaeology: Evaluating 3D Geometric Morphometrics. (19th March 2020) - Dhoop, Thomas; Stark, Sarah; Olaberria, Juan‐Pablo; Whitewright, Julian
Abstract: The analysis of the archaeological remains of ships and boats, in particular hull shapes, have been central to wider analysis of performance, function, and significance within past societies. This article reviews established methods of quantifying shape in ship and boat archaeology—linear measurement ratios and form coefficients—and evaluates the utility of 3D geometric morphometrics (GM). The 3D shape of 30 vessels from north‐west Europe dating between 325 BC and AD 1915 are quantified to study how hull shape relates to a vessel's function and intended operating environment. A comparison of the three methods highlights the importance of analysing the complexity of a hull in a holistic manner and demonstrates that 3D GM outperforms the traditional methods. Abstracto: Cuantificación de la forma de las embarcaciones en arqueología: evaluación de la morfometría geométrica 3D El análisis de los restos arqueológicos de embarcaciones, en particular el de los cascos, ha sido central para la el análisis más amplio del desempeño, la función y la importancia de estas en las sociedades del pasado. Este artículo reseña los métodos establecidos para cuantificar la forma de las embarcaciones en arqueología – proporciones de medidas lineales y coeficientes – y evalúa la utilidad de la morfometría geométrica 3D (GM). Se cuantifica la forma 3D del casco de treinta embarcaciones del noroeste de Europa datadas entre el 325 a.C. y 1915 d.C. para estudiar cómo la misma se relaciona con la función de la embarcación y el ambiente de operación para el cuál fue concebida. Una comparación de tres métodos resalta la importancia de analizar la complejidad del casco de manera holística y demuestra que el GM 3D sobresale con respecto a los métodos tradicionales. Palabras clave : Embarcación, variación de la forma del casco, morfometría geométrica 抽象: 量化考古发现的船形:3D几何形态学的评估 针对考古发现的船只遗存的分析, 特别是对船体形状的分析, 对更广泛探讨其在以往社会中的性能、功能和意义至关重要。本文回顾了已有的量化船形的方法——线性测量比和船型系数——并对3D几何形态学 (GM) 的实用性做了评估。对来自西北欧30艘年代在公元前325年至公元1915年的船只的3D形状定量研究显示出船体形状与船只功能及其工作环境之间关系的紧密程度。三种研究方法的比较凸显了以整体方式分析船体复杂性的重要性, 并证明了3D GM优于传统方法。 关键词:船舶, 船体形状变化, 几何形态。 量化考古發現的船形:3D幾何形態學的評估 針對考古發現的船只遺存的分析, 特別是對船體形狀的分析, 對更廣泛探討其在以往社會中的性能、功能和意義至關重要。本文回顧了已有的量化船形的方法——線性測量比和船型系數——並對3D幾何形態學 (GM) 的實用性做了評估。對來自西北歐30艘年代在公元前325年至公元1915年的船只的3D形狀定量研究顯示出船體形狀與船只功能及其工作環境之間關系的緊密程度。三種研究方法的比較凸顯了以整體方式分析船體複雜性的重要性, 並證明了3D GM優于傳統方法。 關鍵詞:船舶, 船體形狀變化, 幾何形態。